EXPLORATION OF VARIOUS VISUAL DISPLAY METHODS FOR GEOVISUALIZATION PURPOSES - Helik Susilo; Farouki D Rassarandi; Febrian F Susanta; Putra Putra; Siti Komariah (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2020)
Visual display is a technique that utilizes tools on the computer to explore and to present information. There are some variation of visual display methods that have been developed and widely used in the needs of geovisualization and cartography such us Parallel Coordinate Plot (PCP), Space Time Cube (STC), Self-Organize Map (SOM) and Cartogram. This research uses these methods includes definitions and functions, recommendations for using an application and their respective advantages and disadvantages. Applying the right visualization is based on the needs or goals of geovisualization because each visual display has unique characteristics.